“Valve-On-Valve” — an alternative method of surgical treatment of tissue valve dysfunctions - N. V. Rogulina; I. K. Khalivopulo (Российский кардиологический журнал, 2019)
Every year, the frequency of use of biological prostheses for treatment of valvular heart disease increases.The implantation of a biological prosthesis allows avoiding lifelong anticoagulant therapy, but at the same time it may require further replacement due to the dysfunction development.Traditional reoperation is associated with a certain risk of trauma to various structures and cardiac chambers during explantation of non-functioning valve.Transcatheter replacement of the prosthesis (“valve-in-valve”) is not always realizable due to lack of routes for the delivery system and small diameter of the initial valve.“Valve-in-valve” is not always demanded because it does not provide an option to choose mechanical or biological prosthesis.Valve-on-valve implantation technique implies that the new prosthesis is implanted in the carcass of the previous valve. It allows avoiding severe intraoperative complications, reducing the duration of the main stage of the surgery and adverse events in the early postoperative period, and provide an option to choose implantable device.In this review, the authors attempted to comprehensively evaluate the world experience in applying the “valve-on-valve” technique.